2015
DOI: 10.1108/jpbm-04-2014-0548
|View full text |Cite
|
Sign up to set email alerts
|

Social identity, collective self esteem and country reputation: the case of Pakistan

Abstract: Purpose – This paper aims to show how the relative global status of a country influences its internal country reputation and resulting social cognitions of citizens. Design/methodology/approach – The theories of social identity and collective self-esteem were employed to explain how self-assessment and evaluations of a country’s reputation are regulated by social concepts and vice versa. The structural equation modeling technique was emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 57 publications
5
37
1
Order By: Relevance
“…Business partners, such as retailers and suppliers, are actively playing roles with the aim of contributing to the development of the brand identity and the decisions made in the brand team (Törmälä and Saraniemi, 2017). Linked entities, such as endorsers (Dwivedi et al, 2015), other brands (Davies et al, 2006;Delgado-Ballester and Hernández-Espallardo, 2008;Thomas, 2015) or products are sold under the same brand name, such as own labels (Marques dos Santos et al, 2016) and the country or origin (Lu and Xu, 2015;Yousaf and Li, 2015;Brodie and Benson-Rea, 2016). What the press and the media report about the brand and all the publicity produced by what is perceived as reliable sources are not unnoticed when consumers evaluate brands (Gendel-Guterman and Levy, 2017).…”
Section: Other Things Have Changedmentioning
confidence: 99%
“…Business partners, such as retailers and suppliers, are actively playing roles with the aim of contributing to the development of the brand identity and the decisions made in the brand team (Törmälä and Saraniemi, 2017). Linked entities, such as endorsers (Dwivedi et al, 2015), other brands (Davies et al, 2006;Delgado-Ballester and Hernández-Espallardo, 2008;Thomas, 2015) or products are sold under the same brand name, such as own labels (Marques dos Santos et al, 2016) and the country or origin (Lu and Xu, 2015;Yousaf and Li, 2015;Brodie and Benson-Rea, 2016). What the press and the media report about the brand and all the publicity produced by what is perceived as reliable sources are not unnoticed when consumers evaluate brands (Gendel-Guterman and Levy, 2017).…”
Section: Other Things Have Changedmentioning
confidence: 99%
“…As the security conditions in Pakistan deteriorated, western countries imposed a travel ban, preventing their citizens from visiting the country. This led to decreases in both exports and inflows of FDI, as well as damage to the nation's reputation (Hussain 2011;Lopez-Calix and Touqeer 2013;Yousaf and Li 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The self-perception of people living in a certain country is pivotal in building sustainable place brand equity. However, Yousaf and Li (2015) reported that the citizens of negatively perceived countries like Pakistan internalize the negative stereotypes associated with their country. Therefore, in coming years, Pakistan may lose this effective reputation-enhancing tool, unless some revolutionary steps are taken by the government of Pakistan to revive the passion and invoke self-belief of Pakistanis to evolve a collective identity.…”
Section: Discussionmentioning
confidence: 99%